Intelligent glove for suppression of resting tremor in parkinson’s disease - M. Zulkefli, Adibah; Muthalif, Asan G.A.; Nordin, Diyana Nor Hidayati; Syam, Thaer Mahmoud Ibrahim (JVE International, 2019)
One of the significant symptoms in Parkinson’s disease is resting tremor. Resting tremor occurs when the muscle is relaxed, causing the limb to shake. Rhythmic muscle movement of the patients commonly happens within the range of 4 Hz to 6 Hz. Thus, reducing this type of tremor will help improve patients’ quality of life. In this paper, to suppress resting tremors, an intelligent glove was designed utilizing the concepts of vibrations and gyro effect. A rotating brass disc attached to the glove creates a gyroscopic effect of the smart glove. Therefore, the disc will do their utmost to stay upright and counter any input forces instantaneously by providing the counterforce. A reduction of more than 50 % with the intelligent glove is also shown.